Pengaruh Pemahaman Aturan Perpajakan, Motivasi Wajib Pajak dan Pengetahuan Pajak Terhadap Kepatuhan Wajib Pajak - Yokhebed Winni Cintaswara Parengkuan; Vivi Iswanti Nursyirwan (Politeknik Negeri Bengkalis, 2023)
This study aims to determine how the effect of tax knowledge, taxpayer motivation, and tax knowledge on taxpayer compliance. The object of research in this study is an individual taxpayer who is registered at the Tax Service Office of Pratama Kebayoran Lama. This study uses primary data obtained from questionnaire data distributed to respondents of income tax payers. The sampling technique used purposive sampling method by producing 100 samples of individual taxpayers. The data analysis technique used a Structural Equation Model (SEM) approach based on Partial Least Square (PLS) using the SmartPLS 3.3.9 application. The results of the study show that tax knowledge, tax payer motivation, and tax knowledge jointly affect taxpayer compliance. Understanding of tax rules has a positive and significant effect on taxpayer compliance, taxpayer motivation has a positive and significant effect on taxpayer compliance, and tax knowledge also has a positive and significant effect on taxpayer compliance at the Tax Service Office of Pratama Kebayoran Lama.Â Keywords: A understanding of tax rules, taxpayer motivation, tax knowledge, taxpayer compliance